Faktor-Faktor Yang Mempengaruhi Mortalitas Pasien Batu Ginjal yang Menjalani Operasi Nefrolitotomi di RSUD Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2017-2021 - Purnamasari, Haninovita; Hadibrata, Exsa; Mayasari, Diana; Wintoko, Risal (Medula, 2026)
This study aims to determine the factors that influence the mortality of kidney stone patients after nephrolithotomy surgery. This study used an descriptive analytic method with a case control approach. The research sample was 84 people, namely 21 cases and 63 controls in the working area of RSUD Dr. H. Abdul Moeloek 2017-2021 and was taken using the consecuetive sampling method. The dependent variable is the mortality of post-nephrolithotomy kidney stone patients. The independent variables were age, sex, Hb levels, decreased kidney function, types of stones, and multiple comorbidities. Statistical analysis using the chi square test. Based on the results of the study the mortality rate for patient with kidney stones after nephrolitotomy surgery was 7,9%. Most of the respondents were aged <60 years (76.2%), male (52.4%), Hb level >10 g/dl (63.1%), creatinine level <1.5 mg/dl (57.1%), non staghorn stones (54.8%), and multiple comorbidities (57.1%). Variables that influence mortality in postoperative kidney stone patients (α=0,05), namely age (p value <0,001),  Hb level (p value=0,003), decreased kidney function (p value=0,001), type of stone (p value=0,043), and multiple comorbidities (p value=0,002). While the unrelated variables is gender (p value=0,207). The factor that has the most dominant influence is Hb levels. Age, Hb level, decreased kidney function, type of stone and multiple comorbidities are influence with mortality in postoperative kidney stone patients at RSUD Dr. H. Abdul Moeloek.